2015
DOI: 10.1016/j.dnarep.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial alkyltransferase-like (eATL) protein protects mammalian cells against methylating agent-induced toxicity

Abstract: In both pro- and eukaryotes, the mutagenic and toxic DNA adduct O(6)-methylguanine (O(6)MeG) is subject to repair by alkyltransferase proteins via methyl group transfer. In addition, in prokaryotes, there are proteins with sequence homology to alkyltransferases, collectively designated as alkyltransferase-like (ATL) proteins, which bind to O(6)-alkylguanine adducts and mediate resistance to alkylating agents. Whether such proteins might enable similar protection in higher eukaryotes is unknown. Here we express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…However, protection was conveyed predominantly via shielding of alkyl-guanine-induced alkylG:T mispairs from futile rounds of DNA mismatch repair that result in DNA double strand break formation, as also shown in E. coli (36,37). ATL did not initiate NER of methyl-guanine in mammalian cells in these studies (36). Consistently, in E. coli enhanced NER by ATL could only be observed for larger alkyl lesions and not for methyl-guanine (37,38).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, protection was conveyed predominantly via shielding of alkyl-guanine-induced alkylG:T mispairs from futile rounds of DNA mismatch repair that result in DNA double strand break formation, as also shown in E. coli (36,37). ATL did not initiate NER of methyl-guanine in mammalian cells in these studies (36). Consistently, in E. coli enhanced NER by ATL could only be observed for larger alkyl lesions and not for methyl-guanine (37,38).…”
Section: Discussionsupporting
confidence: 73%
“…Finally, previous studies showed that expression of E. coli ATL protects mammalian cells against cytotoxicity of methyl-guanine lesions (36). However, protection was conveyed predominantly via shielding of alkyl-guanine-induced alkylG:T mispairs from futile rounds of DNA mismatch repair that result in DNA double strand break formation, as also shown in E. coli (36,37).…”
Section: Discussionmentioning
confidence: 91%
“…Reactive oxygen and nitrogen species predominantly induce specific base modification, such as 8-oxo-dG, 8-nitro-dG [9] , or GC to TA transversions due to their high reactivity with strong nucleophilic sites on nucleobases [10] . External chemical compounds can introduce particular chemical groups, for example alkylation of DNA by methylnitrosourea [11] or N-methyl-N′-nitro-N-nitrosoguanidine [12] can cause DNA cross-links (e.g. mitomycin C, cisplatin) [13,14] , or enhance formation of single- and double-strand breaks by sealing DNA-topoisomerase complexes [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Repair of O 6 -CMG was first investigated by assessing azaserine mutagenicity in bacteria and yeast with defined deficiencies in repair factors. , Alkyltransferase repair enzymes and NER assisted by alkyltransferase-like (ATL) enzymes ,, protected bacterial and yeast cells from mutations resulting from exposure to azaserine. ATL proteins are homologous to O 6 -methylguanine-DNA methyltransferase (MGMT), but do not have the transferase domain; therefore, they bind DNA at modified bases but do not catalyze their removal. Binding and conformational studies supported that ATL proteins serve as signaling factors of O 6 -alkylG, including O 6 -CMG, to the NER pathway. ,, Although ATLs have not been found in higher eukaryotes yet, these results raise the question of whether alkyltransferases such as MGMT might have a similar role in facilitating and signaling for the repair of O 6 -CMG in higher organisms. However, this speculation has never been confirmed, and the role of MGMT in relation to O 6 -CMG persistence in human cells remains equivocal.…”
Section: Cellular Response To O 6-cmg: Dna Repairmentioning
confidence: 99%